A felnőtt- és szakképzés történetének kutatása elméleti és módszertani kérdések - Kordé, Zoltán (Közép-Európai Közlemények, 2014)
The study examined the history of research on vocational and aduit training comes to the conclusion that in each of the two sectors - especially the period before the eighteenth century - there are gaps in the research. Partly this is due to the fact that neither apropos of adult education, neither in case of vocational training the concept is not clearly clarified, so researchers are often uncertain whether they can use these concepts to earlier eras. On the other hand, researchers often try to draw the antecedents not by the resources, but based on the secondary literature. The study points out, inter alia, that in all cases should be used the sources of the period in question (eg. The Middle Ages), just so we can get to know the set of terms and to determine if any kind of phenomenon can be considered the antecédent of today’s adult and vocational training. We can draw an authentical history of these disciplines only in this way, which in turn could contribute also to clarify the current conceptual and other problems.